2013
DOI: 10.1063/1.4807127
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of SnO2:F/ZnO:Al bi-layer as a front electrode on the properties of p-i-n amorphous silicon based thin film solar cells

Abstract: The effect of aluminum doped zinc oxide film used between a fluorine doped tin oxide layer and a hydrogenated amorphous silicon carbide layer to improve the open circuit voltage (Voc) and fill factor (FF) for high efficiency thin film solar cells. The efficiency enhancement was accomplished by the insertion of high work-function layers engineered in the interfaces to raise FF as well as Voc. Therefore, we were able to obtain the conversion efficiency of 10.34% at 16.14 mA/cm2 of the current density (Jsc) and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The manipulation of the absolute electron energies (with respect to all other materials) is less well understood. The addition of dielectric layers and nanodots have been shown to improve performance and characteristics in several applications [17,18]; however, no consensus has emerged regarding the reasons for their success [19]. Several mechanisms have been put forward.…”
Section: Introductionmentioning
confidence: 99%
“…The manipulation of the absolute electron energies (with respect to all other materials) is less well understood. The addition of dielectric layers and nanodots have been shown to improve performance and characteristics in several applications [17,18]; however, no consensus has emerged regarding the reasons for their success [19]. Several mechanisms have been put forward.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to study the properties of indium–free or indium–reduced TCO thin films for the application in solar cells. Among the possible materials, tin oxide is considered as one of the most promising candidates mainly because of its inexpensive cost, chemically stable in acidic and basic solutions, stable in hydrogen plasma, and mechanically strong, which are important attribute for the fabrication and operation of solar cells 15 16 17 . The undoped SnO 2 thin films have high resistivity due to its stoichiometric nature which could not produce large number of free charge carriers.…”
mentioning
confidence: 99%
“…It has been reported that the high work function of the AZO layer can moderate the abrupt band bending across the AZO/ a-Si:H interface leading to a barrier height lowering and, thus, to a better collection efficiency of hole carriers. 26,27 Therefore, the introduction of the AZO layer may result in the barrier height lowering between the electrode and the p-layer and, thus, yields the better QE loss of the HPS-PV cell.…”
mentioning
confidence: 99%